PENGEMBANGAN KUALITAS PRIBADI KONSELOR SECARA PROFESIONAL DALAM PELAYANAN BIMBINGAN KONSELING: LITERATURE REVIEW - Dwika Sukma Dewi; Lani Cahyani; Happy Karlina Marjo (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
The goal in providing counseling services is to provide conditions which can help clients develop psychological strength to evaluate his behavior now, and can get that behavior now and can get behavior more effective. The process of learning to behave effectively is facilitated by creating warm counseling environment and application of various counseling procedures. To achieve this requires quality interpersonal relationships both between counselor and counselee. Counseling as a profession depicted by the counselor's appearance. A professional counselor is a figure who can present himself as a role model. Among competencies counselor, the most important thing is the personal quality of the counselor, because the counselor used as a person who must be able to display his true identity complete, precise and meaningful, and build good interpersonal relationships so that it becomes the driving force for the success of the service. Personal counselor is wrong one of them is an